REVERSE LOGISTICS OF AGROCHEMICAL PESTICIDE PACKAGING AND THE IMPACTS TO THE ENVIRONMENT - Mello, Mario Fernando; Scapini, Rosangela (Brazilian Journal of Operations & Production Management, 2016)
Abstract: Over time, agriculture has proven to be an important economic development factor for Brazil. The evolution and the need for productivity caused a large increase in the use of pesticides in agriculture and with it, the need to give proper treatment to packaging. With these agricultural activities in evidence, it is not possible to keep the crops without the use of pesticides. In 2000, it was created the 9,974 law as a decree Law 4,074/2002, which regulates the reverse logistics of empty containers of pesticides. This study intends to demonstrate that there are still producers who have difficulties in finding the correct destination to pesticide containers because of lack of knowledge of the law or because they acquire chemicals illegally, without a specific origin. The instruments for protecting the environment, such as licensing and environmental legislation stand out as high points, since it has the general objective of analyzing and demonstrating how reverse logistics helps minimize the impact and the possible environmental and health problems caused by the incorrect disposal of pesticide containers of and along with a group of farmers.